Chitosan-Dextran sulfate coated doxorubicin loaded PLGA-PVA-nanoparticles caused apoptosis in doxorubicin resistance breast cancer cells through induction of DNA damage - Sumit Siddharth (Nature Portfolio, 2017)
Abstract To overcome the toxicity, pharmacokinetics and drug resistance associated with doxorubicin (DOX), a strategy was developed by encapsulating DOX- loaded-PLGA-PVA- nanoparticles within chitosan-dextran sulfate nanoparticles (CS-DS) [CS-DS-coated-DOX-loaded -PLGA-PVA-NP] and study the sensitivity against DOX- resistance- breast cancer cells (MCF-7-DOX-R). These CS-DS and PLGA-PVA double coated DOX are spherical, stable, polydispersed and have zeta potential +2.89 mV. MCF-7- DOX-R cells were derived by exposing increasing doses of DOX in MCF-7 cells. These cells were resistance to 500 nM of DOX while parental cells were susceptible at 150 nM. The double coated NP caused more cytotoxicity in cancer and MCF-7-DOX-R cells without affecting the normal cells in comparison to DOX-loaded-PLGA-PVA-NP. These NP enhances the uptake of DOX in MCF-7-DOX-R cells and caused apoptosis by increasing apoptotic nuclei, Bax/Bcl-xL ratio, cleaved product PARP-1, tumor suppressor gene p21, p53, topoisomerase inhibition activity, DNA damage and decreasing the migratory potential of cells. An increased S phase arrest was noted in DOX and DOX- loaded- PLGA-PVA-NP treated cells but reduction of S phase and simultaneous increase of Sub-G1 was observed in double coated-NP. Thus, data revealed that CS-DS- DOX- loaded PLGA-PVA- NP caused DOX-resistance cell death by inducing inhibition of topoisomerase activity followed by DNA damage.